Factors Related to Clean and Healthy Living Behavior (PHBS) in Students - Nst, Izza Azzahra; Ashar, Yulia Khairina; Siregar, Putra Apriadi (Indonesian Journal of Global Health Research, 2024)
Clean and healthy living behavior (PHBS) is essential for achieving optimal health. School-age children are in a crucial period for initiating PHBS, enabling them to become health promoters for their families, school environment, and society. Implementing PHBS in schools can raise public awareness, encouraging clean and healthy living. This research aims to identify factors related to PHBS among students. The study employs a quantitative, cross-sectional design. The population consists of 298 students, with a sample of 89 respondents selected based on inclusion criteria, specifically fifth and sixth graders registered at SD Negeri 066650 Medan, using the Lameshow formula. Conducted at SDN 066650 Medan from January to March 2024, the research utilizes a questionnaire distributed directly to students. Examined variables include knowledge, attitudes, infrastructure, and the role of teachers. Data analysis involves Univariate and Bivariate methods, processed with the chi-square test using SPSS version 20. Results indicate significant relationships between knowledge (p=0.033), attitudes (p=0.033), infrastructure (p=0.035), and teacher roles (p=0.019) with PHBS implementation in schools. The study concludes that low levels of knowledge, attitudes, infrastructure availability, and active teacher involvement contribute to inadequate student behavior in practicing PHBS effectively at school.